Effects of athletic training on the spinal curvature in child athletes - Betsch, Marcel; Furian, Thimm; Quack, Valentin; Rath, Bjoern; Wild, Michael; Rapp, Walter (Research in Sports Medicine, 2015)
The purpose of this study was to examine the spinal posture in young athletes depending on training intensity. The spinal curvature of 245 children, age 8 to 12 years, was evaluated using rasterstereography. According to their weekly training time group 1 (mean age: 9.54 ± 1.18) did 2-6, group 2 (mean age: 9.49 ± 0.87) did 6-15 and group 3 (mean age: 9.68 ± 0.87) did over 15 hours of training. Group 1 had a significantly higher weight (p = 0.028) (33.86 ± 7. kg) than those of the more active groups (30.67 ± 6.49 kg and 29.46 ± 4.33 kg). The mean kyphotic angle decreased significantly (p < 0.001) with the amount of training per week from 46.86 ± 8.2° in group 1 to 40.08 ± 8° in group 3. We also found a significant decrease (p = 0.047) in lateral deviation with training from group 1 with 5.3 ± 3 mm to group 2 with 4.1 ± 1.6 mm. The results of our study suggest that higher training time can be associated with lower weight and decreases in thoracic kyphosis and lateral deviation of the spine.
CRIS-Team Scopus Importer:2022-07-20
Keywords: children; lumbar spine; schoolchildren; training; training frequency; trunk posture